Ultar Violet Curing Of Rubberwood Fibres - Unsaturated Pol Yestercomposites - Poo Palam, Kosheela Devi (2005)

(untitled)
Kajian ini telah dijalankan untuk mengkaji sifat-sifat fizikal dan mekanikal komposit gentian semulajadi yang mempunyai sifat nilai tambah ya:lg dihasilkan melalui teknik pematangan mesra alam iaitu sinaran ultra-ungu (UV) (Iampu UV merkuri piawai digunakan). Resin poliester tak tepu digunakan sebagai polimer matriks bersama dengan pemula foto bisasilfosfin oksida. Gentian kayu getah dari pemulpa termomekanikal (TMP) dipilih sebagai gentian penguat This research project was carried out to study the physical and mechanicai properties of value added bic-fibre composites made by employing environmentally benevolent ultra violet (UV) curing technique. Standard mercury UV lamp was used for the investigation. Unsaturated polyester resin along with bisacylphosphine oxide was used as polymer matrix. Rubberwood fibre (TMP fibres) residues, a waste and un utilized fibre from one of the medium density fibre board (MDF) plants, were used as reinforcement fibres.